Polyfunkční dům Brno - Líšeň - Horenský, Dominik (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Předmětem bakalářské práce je zpracování projektové dokumentace polyfunkční domu v Brně - Líšni. Objekt má 4 nadzemní podlaží a 2 podzemní podlaží. V prvním nadzemním podlaží se nachází 2 pronajímatelné prostory (obchody). Ve 2-4 nadzemním podlaží se také nachází pronajímatelné prostory (doktoři a administrativa). V 1.PP se nachází prostor kavárny na západní části a zbylá část je obsazena pronajímatelným prostorem. Ve 2.PP se nachází podzemní parkování. Vjezd do 2.PP je zajišťen rampou v severní části přilehlé k silnici. Nosným systémem je železobetonový skelet. Střechy jsou navrženy jako ploché jednoplášťové. Objekt je založen na ŽB patkách v kombinaci s ŽB pasy.

The aim of the bachelor's thesis was to create the documentation for building permission for polyfunctional building located in Brno-Líšeň. Building has four floors and two underground floors. On the ground floor are two leasable spaces (shops). In the 2-4 upper floor are also leasable spaces (doctors, offices). In the first underground floor is cafe. It's in the west part of the building. The rest of that floor is leasable space. In the second underground floor are parking spaces. The entrance to the 2nd underground floor is secured by outdoor ramp located on the north side of the building connected to the main road. Structural system of building is cast-in-place reinforced concrete frame. The roofs of the building are all designed as warm flat roofs. Object is based on simple foundation pads and strip foundations.
Multifunctional building Brno - Líšeň
Keywords: polyfunkční dům; Brno-Líšeň; monolitický železobetonový skelet; jednoplášťová plochá střecha; administrativa; obchody; služby; podzemní parkování; předsazená fasáda; polyfunctional building; Brno-Líšeň; cast-in-place reinforced concrete; warm flat roof; office; shops; services; underground parking; curtain wall